Effects of Hydration and a Hyaluronic Acid-Containing Lozenge on Voice Parameters in Conjunction With a Vocal Loading Test - Pilsl, Theresa; Köberlein, Marie; Kirsch, Jonas; Döllinger, Michael; Echternach, Matthias (Journal of Speech Language and Hearing Research, 2025)
PURPOSE: This study explores the effects of water intake and a hyaluronic acid (HA)-containing lozenge on acoustic measurements and vocal oscillation patterns investigated after a vocal loading test (VLT). METHOD: Ten healthy subjects (five females, five males) read out loud a standardized text for 10 min at a target level of 80 dB(A), measured 30 cm from the mouth, under three conditions but each after fasting for 2 hr: (a) drinking 0.7 l of water, (b) sucking an HA-containing lozenge, and (c) neither of both before the VLT. The dysphonia severity index (DSI) was assessed before and after the reading task. Additionally, high-speed videolaryngoscopy (HSV), electroglottography, and an audio signal during sustained phonation on the vowel /i/ before and after the VLT were analyzed. The glottal area waveform was derived from the HSV footage. RESULTS: DSI values decreased for the H2O and HA group, but reached statistical significance only for the H2O condition, while remaining stable for the control condition. These DSI decreases were driven by increases in minimum sound pressure level intensity (Imin)-again with statistical significance solely for the water intake intervention. Statistically nonsignificant changes were observed regarding periodicity and perturbation parameters across all conditions. No phase differences or aperiodicities were apparent in the phonovibrograms. CONCLUSIONS: Hydration and an HA lozenge did not significantly alter vocal fold biomechanics after a VLT. However, the decrease in DSI values with increased Imin suggests a reduced vocal capacity for the H2O condition. SUPPLEMENTAL MATERIAL: https://doi.org/10.23641/asha.28271285.
CRIS-Team Scopus Importer:2025-02-28